Na contramão da ordem vigente : a mulher no contexto da ditadura militar em Tropical Sol da Liberdade, de Ana Maria Machado - Jacomel, Mirele Carolina Werneque (2008)
This research had as objective analyzes the feminine character's representation in the romance Tropical Sol da Liberdade and to look for theoretical contributions that sustain that discussion. For so much, it was fundamental to accomplish an exam concerning the thematic of the work to understand better as the literature it is also the expression of a historical moment. In this way, seeking protection in the presuppositions of the Feminist Critic, we wove considerations on the relationship Literature and History, on the history of the women's oppression in Brazil, the collision of the literature of feminine authorship and the literary canon as one of the proposals of desconstrução of the Post-structuralism, besides discussing the participation, direct or indirect, of the woman in the actions against the military government of 1964. To leave of that exam of the historical processes, we built an analysis of the literature of feminine authorship, traveling the history of the Brazilian writers' literary production and, with that, we accomplished notes around the different ways of the woman's representation in the literature. Finally, we used the whole debate assimilated to contribute with the reading of the character protagonist's of Ana Maria Machado referred romance representation.